Correlation between Dominant Working Styles of Students at the Faculty of Technology and Metallurgy in Skopje and their Curriculum Choice (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
This paper aims to detect the advantages and disadvantages of Working Styles in general, determining and interpreting dominant Working Styles of students in different curricula at The Faculty of Technology and Metallurgy in Skopje. The research was conducted using Julie Hay's questionnaire to determine working styles. The aim was to recognise individual characteristics reflected through the specific Working Style, i.e. the characteristic pattern for a series of expected behaviours - script pattern. These results were summarised for each group of students from six curricula, and a detailed analysis was made. Advantages, disadvantages, and essential steps were listed to increase the advantages and minimise the disadvantages. Also, recommendations that would motivate further utilisation of their potential were given. This established the connection between the manifested Working Styles of the groups of students and the choice of the corresponding curriculum. This work is expected to improve curricula and teaching methods for the benefit of current and future students in choosing their future profession, including their interests, skills and abilities for building a career as engineers.